Construction and Validation of an Occupational Risks Scale for Intra-hospital Nursing Staff - Cuadros-Carlesi, Katya; Henríquez-Roldán, Carlos; Meneses Ciuffardi, Elena; Fuentes Ibáñez, Jaime; Ruiz-Araya, Paola (Investigación y Educación en Enfermería, 2023)
Objective. To construct and evaluate initial validity indicators of an instrument on occupational risks for hospital nursing staff. Methods. A methodological study was conducted in four Chilean hospitals. The study was carried out in three stages: (i) integrative literature review on risk assessment instruments for nursing; (ii) descriptive qualitative study on 113 health professionals to identify their work conditions and experiences regarding occupational risks and construct three instruments proposals for nursing managers, clinical nurses, and technicians; and (iii) validity and reliability study of the three instruments in 503 nurses and nursing technicians. To collect the data from the qualitative study, individual interviews, focal groups, and non-participant observation were conducted. The data were analyzed thematically into predefined risk categories. Content validation was performed through expert judgment, and exploratory factor analysis of principal components was conducted for the preliminary construct validity study. Cronbachs alpha was used as an indicator of internal consistency. Results. A total of 128 items were identified, distributed across 11 categories and 25 subcategories of occupational risks for the three instruments derived from the original proposal. After expert validation, pilot study, and instrument administration, Cronbach's alpha values between 0.88 and 0.93 were obtained. Exploratory factor analysis distinguished eight to eleven components, with unsatisfactory goodness-of-fit indicators. Conclusion. The instruments demonstrated good parameters of content validity and reliability, although their construct validity needs further improvement.